"The Looming, Crazy Stalker Coronavirus": Fear Mongering, Fake News, and the Diffusion of Distrust. (June 2021) - Ravenelle, Alexandrea J.; Newell, Abigail; Kowalski, Ken Cai
The authors explore media distrust among a sample of precarious and gig workers interviewed during the COVID-19 pandemic. Although these left-leaning respondents initially increased their media consumption at the outset of the pandemic, they soon complained of media sensationalism and repurposed a readily available cultural tool: claims of "fake news." As a result, these unsettled times have resulted in a "diffusion of distrust, " in which an elite conservative discourse of skepticism toward the media has also become a popular form of compensatory control among self-identified liberals. Perceiving "fake news" and media sensationalism as "not good" for their mental health, respondents also reported experiencing media burnout and withdrawing from media consumption. As the pandemic passes its one-year anniversary, this research has implications for long-term media coverage on COVID-19 and ongoing media trust and consumption.